THE IMPLEMENTATION OF MUSYARAKAH FINANCING IN ISLAMIC BANKS IN INDONESIA IN RELATION TO DEFAULTS BUSINESS PARTNERS - Sumiati, Sumiati; Akmaliyah, Akmaliyah (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This research aims to analyze the implementation of musyarakah financing in Islamic banks in Indonesia related to the default of business partners.Â The principal banking law states that the function of banking in Indonesia is to collect and distribute funds. Islamic banking law regulates various types of financing, including musyarakah financing. The method used in this research is descriptive analytical method using qualitative approach. The results of this research discussion show that legal protection for the parties in musyarakah financing in the event of default by business partners consists of: first, legal protection provided by law, namely protected by the Banking Law, especially Articles 1, 7 and 8, second, legal protection based on musyarakah contracts/agreements, in the form of : First, if the business partner has been classified into the collectibility of bad debts, the bank can confiscate the collateral and then proceed with the auction. Second, submitting the dispute to a Islamic arbitration body or court. Meanwhile, the efforts of Islamic banks if there are indications that there will be defaults by business partners in musyarakah financing are to addendum the contract.